Curable composition, cured product, overcoat film for flexible wiring board, flexible wiring board, and method for producing flexible wiring board

By developing a curable composition without fluorine atoms, using polyisocyanate-derived polyurethane and olefin defoaming agents, the disconnection inhibition, low warpage and defoaming properties of the flexible wiring board are improved, and the prior art has been solved Problems of insufficient physical properties and the use of fluorine-containing compounds.

CN119307169APending Publication Date: 2025-01-14NIPPON POLYTECH CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410937261.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-13
Filing Date
2024-07-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The curable composition used in the protective film of the existing flexible wiring board has room for improvement in terms of disconnection inhibition, low warpage, flexibility and defoamability, and there is a risk of using fluorine-containing compounds such as PFAS, which requires Develop excellent physical compositions without fluorine atoms.

Method used

A curable composition containing polyurethane derived from a carboxy group and an aromatic ring concentration of 0.1 to 6.5 mmol/g, a solvent, a compound having two or more epoxy groups in one molecule, and an olefin defoaming agent is used to ensure the composition. No fluorine atoms.

Benefits of technology

A curable composition with excellent disconnection inhibition, low warpage and defoaming properties is achieved, and the use of fluorine-containing compounds is avoided, and it is suitable for the outer coating film and manufacturing method of flexible wiring boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004941705880000021
    Figure BDA0004941705880000021
  • Figure BDA0004941705880000031
    Figure BDA0004941705880000031
  • Figure BDA0004941705880000032
    Figure BDA0004941705880000032
Patent Text Reader

Abstract

The invention provides a curable composition, a cured product, an overcoat film for a flexible wiring board, a flexible wiring board, and a method for manufacturing the flexible wiring board, wherein the curable composition is excellent in wire breakage inhibition, low warping, flexibility and defoaming property, and does not contain fluorine atoms. The present invention provides: a polyurethane which contains (component a) a polyurethane that has a carboxyl group, has an aromatic ring concentration of 0.1-6.5 mmol / g, and contains an organic residue derived from a polyisocyanate; (Component b) a solvent; (Component c) a compound having two or more epoxy groups in one molecule; and (component d) a defoaming agent containing an olefin and not containing a fluorine atom, a cured product, an overcoat film for a flexible wiring board, a flexible wiring board, and a method for producing a flexible wiring board.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable composition, a cured product, an outer coating film for a flexible wiring board, a flexible wiring board, and a method for producing a flexible wiring board. Background Art

[0002] In the past, the surface protective film of the flexible wiring circuit included the following types: a type in which a polyimide film called a cover film is prepared and punched into a mold that matches the pattern, and then pasted with an adhesive; and a type in which a flexible ultraviolet curing type or thermosetting type outer coating agent is applied by screen printing, and the latter is particularly useful in terms of workability. As these curing type outer coating agents, resin compositions mainly composed of epoxy resins, acrylic resins, or composites thereof are known. Most of them are mainly composed of modified resins, especially those that have been introduced with a butadiene skeleton, a siloxane skeleton, a polycarbonate diol skeleton, a long-chain aliphatic skeleton, etc.

[0003] However, in recent years, as electronic devices have become lighter and smaller, flexible substrates have also been made thinner and lighter, and there has been a strong demand for improvements in the physical properties of overcoat resin compositions.

[0004] As a technique related to these, for example, Patent Document 1 discloses a curable composition containing polyurethane, a solvent, and a compound having two or more epoxy groups in one molecule, regarding a composition that can be used for a protective film of a flexible wiring board.

[0005] Patent Document 2 discloses a curable polyurethane composition comprising a curable polyurethane resin (A) and a defoaming agent (B) as essential components, and using an ethylene-α-olefin cooligomer as the defoaming agent (B).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 6912385

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 05-247161 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] However, there is room for further improvement regarding the curable composition used in the protective film. For example, for the physical properties such as the defoaming property of the curable composition used in the protective film etc. for making the curing material such as the flexible wiring board wiring, it is expected to be further improved. In addition, from the viewpoint of safety, it is expected to control the use of fluorinated compounds such as PFAS (organic fluorine compounds) as much as possible. From such a viewpoint, it is expected to develop a curable composition that does not contain fluorine atoms and can play an excellent physical property.

[0012] In view of the above circumstances, an object of the present invention is to provide a curable composition, a cured product, an outer coating film for a flexible wiring board, a flexible wiring board, and a method for producing a flexible wiring board, which are excellent in disconnection suppression, low warpage, flexibility and defoaming properties and do not contain fluorine atoms.

[0013] Solutions to technical problems

[0014] The present inventors have repeatedly conducted studies to solve the above-mentioned technical problems, and as a result, have discovered a curable composition comprising (component a) a polyurethane having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, and containing an organic residue derived from a polyisocyanate; (component b) a solvent; (component c) a compound having two or more epoxy groups in one molecule; and (component d) a defoaming agent containing an olefin and not containing fluorine atoms, thereby completing the present invention.

[0015] That is, the present invention is as follows.

[0016] <1>

[0017] A curable composition free of fluorine atoms, comprising:

[0018] (Component a) a polyurethane having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, and containing an organic residue derived from a polyisocyanate;

[0019] (component b) a solvent;

[0020] (Component c) a compound having two or more epoxy groups in one molecule; and

[0021] (Component d) A first defoaming agent comprising an olefin.

[0022] <2>

[0023] according to <1> The curable composition, wherein

[0024] Component a is a polyurethane having a structural unit represented by formula (1),

[0025] [Chemical formula 1]

[0026]

[0027] <3>

[0028] according to <1> or <2> The curable composition, wherein

[0029] Component a is a polyurethane having a structural unit represented by formula (2),

[0030] [Chemical formula 2]

[0031]

[0032] In the formula, R 1 Each independently represents a phenylene group or a phenylene group having a substituent.

[0033] <4>

[0034] according to <1> or <2> The curable composition, wherein

[0035] Component a is a polyurethane having a structural unit represented by formula (3),

[0036] [Chemical formula 3]

[0037]

[0038] In the formula, n R 1 Each independently represents a phenylene group or a phenylene group having a substituent, and (n+1) R 2 Each independently represents an alkylene group having 3 to 9 carbon atoms, and n is a natural number of 50 or less.

[0039] <5>

[0040] according to <1> or <2> The curable composition, wherein

[0041] In component a, the organic residue derived from the cyclic aliphatic polyisocyanate accounts for 70 mol% or more of the total amount of the organic residue derived from the polyisocyanate.

[0042] <6>

[0043] according to <1> or <2> The curable composition, wherein

[0044] The content of component a is 60 to 99.9% by mass based on the total amount of component a and component c.

[0045] <7>

[0046] according to <1> or <2> The curable composition, wherein

[0047] The content of component b is 25 to 75% by mass based on the total amount of component a, component b and component c.

[0048] <8>

[0049] according to <1> or <2> The curable composition, wherein

[0050] The number average molecular weight of component a is 3,000 to 50,000, and the acid value of component a is 10 to 70 mgKOH / g.

[0051] <9>

[0052] according to <1> or <2> The curable composition further comprises:

[0053] (Component e) A second defoaming agent comprising an acrylic resin and / or a methacrylic resin.

[0054] <10>

[0055] according to <9> The curable composition, wherein

[0056] The total amount of component d and component e is 0.01 to 3% by mass.

[0057] <11>

[0058] according to <9> The curable composition, wherein

[0059] When the total amount of the components excluding the content of the component b from the total amount of the curable composition is taken as 100% by mass, the total amount of the components d and e is 0.01 to 5% by mass.

[0060] <12>

[0061] according to <9> The curable composition, wherein

[0062] The content of component e is 1 to 150% by mass based on component d.

[0063] <13>

[0064] according to <1> or <2> The curable composition further comprises:

[0065] (Component f) At least one type of fine particles selected from inorganic fine particles and organic fine particles.

[0066] <14>

[0067] according to <13> The curable composition, wherein

[0068] Component f includes silicon dioxide fine particles.

[0069] <15>

[0070] according to <13> The curable composition, wherein

[0071] Component f comprises hydrotalcite particles.

[0072] <16>

[0073] A solidified material, which is <1> or <2> A cured product of the curable composition.

[0074] <17>

[0075] An outer coating film for a flexible wiring board, comprising <16> The solidified material.

[0076] <18>

[0077] A flexible wiring board is formed by forming wiring on a flexible substrate, and a part or all of the surface of the flexible wiring board on which the wiring is formed is <17> The flexible wiring board is obtained by covering with an outer coating film.

[0078] <19>

[0079] A method for manufacturing a flexible wiring board covered with an outer coating film, comprising:

[0080] (Step A) Printing a portion or all of the surface of the flexible wiring board on which wiring is formed by forming wiring on the flexible substrate <1> or <2> The curable composition is used to form a printed film on the wiring;

[0081] (Step B) a step of evaporating part or all of the solvent in the printed film by placing the printed film obtained in step A in an atmosphere of 40° C. to 100° C.; and

[0082] (Step C) A step of curing the printed film obtained in the step A or the printed film obtained in the step B by heating at 100° C. to 170° C. to form an overcoat film.

[0083] Effects of the Invention

[0084] According to the present invention, there can be provided a curable composition, a cured product, an overcoat film for a flexible wiring board, a flexible wiring board, and a method for producing a flexible wiring board, which are excellent in disconnection suppression, low warpage, flexibility, and defoaming properties and do not contain fluorine atoms. DETAILED DESCRIPTION

[0085] Hereinafter, a specific embodiment of the present invention (hereinafter referred to as "this embodiment") is described in detail. The following this embodiment is an example for illustrating the present invention and is not intended to limit the present invention to the following contents. The present invention can be appropriately modified and implemented within the scope of its purpose.

[0086] <Curable Composition>

[0087] The curable composition of the present embodiment is a curable composition comprising (component a) a polyurethane having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, and containing an organic residue derived from a polyisocyanate; (component b) a solvent; (component c) a compound having two or more epoxy groups in one molecule; and (component d) a first defoaming agent containing an olefin, and containing no fluorine atoms. Each component is described below.

[0088] (ingredient a)

[0089] Component a is a polyurethane having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, and contains an organic residue derived from a polyisocyanate. Polyurethane is defined as a substance having a plurality of urethane bonds.

[0090] Examples of the aromatic ring structure of component a include a benzene ring structure, a biphenyl structure, a naphthalene structure, and a fluorene structure.

[0091] The aromatic ring concentration of component a is 0.1 to 6.5 mmol / g, and its lower limit is preferably 0.5 mmol / g or more, more preferably 1.6 mmol / g or more, further preferably 2.0 mmol / g or more, and further preferably 2.5 mmol / g or more. In addition, its upper limit is preferably 6.3 mmol / g or less, more preferably 6.0 mmol / g or less, and further preferably 5.8 mmol / g or less.

[0092] In addition, when showing an example of a preferred combination of the upper limit and the lower limit, 0.1 to 6.5 mmol (i.e., 0.1 to 6.5 mmol / g) is contained relative to 1 g of component a, preferably 0.1 to 6.3 mmol (i.e., 0.1 to 6.3 mmol / g) is contained relative to 1 g of component a, more preferably 0.5 to 6.3 mmol (i.e., 0.5 to 6.3 mmol / g) is contained relative to 1 g of component a, further preferably 1.6 to 6.0 mmol (i.e., 1.6 to 6.0 mmol / g) is contained relative to 1 g of component a, and further preferably 2.0 to 6.0 mmol (i.e., 2.0 to 6.0 mmol / g) is contained relative to 1 g of component a. By making the aromatic ring concentration of component a within the above range, it is easy to achieve a balance between the solvent resistance of the outer coating film of the present embodiment described later and the disconnection suppression property, warping, etc. of the flexible wiring board of the present embodiment described later (however, the action and effect of the present embodiment are not limited to this).

[0093] It should be noted that the aromatic ring concentration can be calculated from the feed ratio or by using 1 H-NMR, 13 After the structure was confirmed by C-NMR and IR,1 The number of protons derived from the aromatic rings was compared with the number of protons derived from the unit by H-NMR (using 1 H-NMR integrated curves for comparison).

[0094] It should be noted that, as the number of aromatic rings in this specification, the aromatic ring is counted as 1, and the condensed ring is also counted as 1. For example, as described below, the benzene ring of formula (51) is counted as 1. The biphenyl structure of formula (52) and the 9H-fluorene structure of formula (53) have two benzene rings, so the number of aromatic rings is counted as 2. The naphthalene structure of formula (54) is counted as 2. Similarly, the anthracene structure (formula (55)) and the phenanthrene structure (formula (56)) are counted as 3. The triphenylene structure (formula (57)) and the binaphthyl structure (formula (58)) are counted as 4.

[0095] It should be noted that the number of circles in formula (51') to formula (58') represents the number of aromatic rings in formula (51) to formula (58), respectively.

[0096] [Chemical formula 4]

[0097]

[0098] [Chemical formula 5]

[0099]

[0100] [Chemical formula 6]

[0101]

[0102] [Chemical formula 7]

[0103]

[0104] [Chemical formula 8]

[0105]

[0106] [Chemical formula 9]

[0107]

[0108] [Chemical formula 10]

[0109]

[0110] [Chemical formula 11]

[0111]

[0112] [Chemical formula 12]

[0113]

[0114] [Chemical formula 13]

[0115]

[0116] [Chemical formula 14]

[0117]

[0118] [Chemical formula 15]

[0119]

[0120] [Chemical formula 16]

[0121]

[0122] [Chemical formula 17]

[0123]

[0124] [Chemical formula 18]

[0125]

[0126] [Chemical formula 19]

[0127]

[0128] The manufacturing method of component a is not particularly limited, and can be synthesized by, for example, reacting a polyisocyanate compound, a carboxyl-containing diol, a polyol other than a carboxyl-containing diol, a monohydroxy compound as required, and a monoisocyanate compound in the presence or absence of a known urethanization catalyst such as dibutyltin dilaurate, using a solvent. When the reaction is carried out without a catalyst, the physical properties of the outer coating film of the present embodiment described later, such as wire breakage inhibition, flexibility, and low warpage, are improved, and therefore it is preferred.

[0129] The structure of component a is not particularly limited as long as it is a polyurethane having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g and containing an organic residue derived from a polyisocyanate. It preferably has at least one of the structural units of formula (1) and the structural units of formula (2), and more preferably has both.

[0130] [Chemical formula 20]

[0131]

[0132] [Chemical formula 21]

[0133]

[0134] (Among them, R 1 Each independently represents a phenylene group or a phenylene group having a substituent.)

[0135] In addition, component a is preferably a polyurethane having a structural unit represented by formula (3). More specifically, it is more preferred that a part or all of the structural unit of formula (2) exists in the polyurethane as a part of the structural unit represented by formula (3).

[0136] [Chemical formula 22]

[0137]

[0138] (Among them, n R 1 Each independently represents a phenylene group or a phenylene group having a substituent, and (n+1) R 2 Each independently represents an alkylene group having 3 to 9 carbon atoms, and n is a natural number of 50 or less. )

[0139] It should be noted that R in formula (2) and formula (3) 1 Each independently represents a phenylene group or a phenylene group having a substituent, preferably a phenylene group. Examples of the substituent include an alkyl group having 1 to 5 carbon atoms, a halogen atom, etc. Among them, from the viewpoint of being free of fluorine, especially free of halogen, the substituent is preferably not a fluorine atom, and more preferably not a halogen atom.

[0140] R 2 Each independently represents an alkylene group having 3 to 9 carbon atoms, and R 2 The number of carbon atoms is preferably 3 to 8, and the number of carbon atoms is more preferably 4 to 8.

[0141] Examples of the compound having the structural unit of the formula (1) include 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene represented by the formula (4).

[0142] [Chemical formula 23]

[0143]

[0144] Examples of the compound having the structural unit of formula (3) include polyester polyols containing a combination of at least one selected from the following dicarboxylic acids and at least one selected from the following diols.

[0145] Examples of the dicarboxylic acid include phthalic acid, isophthalic acid, terephthalic acid, 3-methyl-benzene-1,2-dicarboxylic acid, 4-methyl-benzene-1,2-dicarboxylic acid, 4-methyl-benzene-1,3-dicarboxylic acid, 5-methyl-benzene-1,3-dicarboxylic acid, and 2-methyl-benzene-1,4-dicarboxylic acid. Only one of these may be used, or two or more of them may be used.

[0146] Examples of the diol include 1,3-propylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,8-octanediol, 1,9-nonanediol, 2,4-diethyl-1,5-pentanediol, and 2-ethyl-2-butyl-1,3-propanediol. Only one of these may be used, or two or more of them may be used.

[0147] As the dicarboxylic acid, preferred dicarboxylic acids include phthalic acid, isophthalic acid, terephthalic acid, 3-methyl-benzene-1,2-dicarboxylic acid, and 4-methyl-benzene-1,2-dicarboxylic acid, and phthalic acid is more preferred.

[0148] Moreover, as a diol, as a preferable diol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 3-methyl-1,5-pentanediol are mentioned, and 1,6-hexanediol and 3-methyl-1,5-pentanediol are more preferable.

[0149] As the polyester polyol having the structural unit of formula (3), a polyester polyol having a number average molecular weight of 800 to 5,000 is preferably used, more preferably 800 to 4,000, and even more preferably 900 to 3,500.

[0150] As the polyester polyol having the structural unit of the formula (3), one type of polyester polyol may be used alone, or two or more types may be used in combination.

[0151] The carboxyl-containing diol used as the raw material of component a is not particularly limited as long as it is a compound having one or more carboxyl groups and two alcoholic hydroxyl groups in the molecule. Specific examples of carboxyl-containing diols include dimethylol propionic acid, 2,2-dimethylol butyric acid, N,N-bis(hydroxyethyl)glycine, etc. Among them, from the viewpoint of solubility in the component a synthesis reaction solvent, dimethylol propionic acid and 2,2-dimethylol butyric acid are preferred. These carboxyl-containing diols can be used alone or in combination of two or more.

[0152] When a low molecular weight polyol is used as a polyol other than the polyester polyol having a structural unit of formula (3) and the carboxyl group-containing diol, for example, 1,2-propylene glycol, 1,3-butanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, diethylene glycol, dipropylene glycol, glycerol, trimethylolpropane, etc. can be used alone or in combination of two or more. Preferably, 1,6-hexanediol and 3-methyl-1,5-pentanediol are used.

[0153] The polyisocyanate compound used in the synthesis of component a is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyisocyanate compounds include 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, norbornane diisocyanate, and cyclic aliphatic polyisocyanates such as the biuret form of isophorone diisocyanate; 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, diphenylmethane-4,4'-diisocyanate , 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate and other polyisocyanates having aromatic rings; chain aliphatic polyisocyanates such as biuret of hexamethylene diisocyanate, lysine triisocyanate, lysine diisocyanate, hexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate and 2,2,4-trimethylhexane methylene diisocyanate; polyisocyanates having heterocyclic rings such as isocyanurate of isophorone diisocyanate and isocyanurate of hexamethylene diisocyanate, etc. These may be used alone or in combination of two or more.

[0154] Among them, in order to maintain high heat resistance and electrical insulation performance of the cured product of the present embodiment described later, it is preferred that 70 mol% or more of cyclic aliphatic polyisocyanate is contained relative to the total amount of isocyanate (that is, in component a, the organic residue derived from cyclic aliphatic polyisocyanate is 70 mol% or more relative to the total amount of organic residue derived from polyisocyanate), more preferably 80 mol% or more, and even more preferably 90 mol% or more.

[0155] Among these cyclic aliphatic polyisocyanates, preferred cyclic aliphatic polyisocyanates include isophorone diisocyanate, methylenebis(4-cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane and norbornane diisocyanate, more preferred are methylenebis(4-cyclohexyl isocyanate), isophorone diisocyanate and norbornane diisocyanate, and even more preferred is methylenebis(4-cyclohexyl isocyanate).

[0156] As the raw material of component a, as the monohydroxy compound used as required, as long as there is 1 alcoholic hydroxyl group in the molecule, and there is no particular restriction on the compound of the substituent group that is more reactive with isocyanate group than alcoholic hydroxyl group. As the specific example of the monohydroxy compound, methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, sec-butyl alcohol, tert-butyl alcohol, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monoisobutyl ether, dipropylene glycol monopropyl ether, methyl ethyl ketone oxime etc. can be enumerated.

[0157] These monohydroxy compounds may be used alone or in combination of two or more.

[0158] As the raw material of component a, the monoisocyanate compound used as required can be cyclohexyl isocyanate, octadecyl isocyanate, phenyl isocyanate, toluyl isocyanate, etc. In consideration of the color change resistance of the curable composition of this embodiment when heated, cyclohexyl isocyanate and octadecyl isocyanate are preferred.

[0159] In order to maintain the electrical insulation performance of the cured product of the present embodiment described later at a high level and to maintain the heat resistance at a high level, it is preferred that the polyol side of the raw material contain an aromatic ring, and it is more preferred that the aromatic ring be contained only on the polyol side of the raw material, and that the polyisocyanate of the raw material contain no aromatic ring (i.e., a polyisocyanate having an aromatic ring is not used in the raw material). In the method for manufacturing component a, the blending amount of each component is as follows.

[0160] When a compound having a structural unit of formula (1) is used, the amount of the compound having a structural unit of formula (1) is preferably 3 to 20% by mass, more preferably 5 to 15% by mass, relative to the total amount of the raw materials of component a. When the amount of the compound having a structural unit of formula (1) is 3 to 20% by mass relative to the total amount of the raw materials of component a, a balance between low warpage and disconnection suppression effect of the flexible wiring board covered by the outer coating film of the present embodiment described later can be achieved.

[0161] When a polyester polyol having a structural unit of formula (3) is used, the amount of the polyester polyol having a structural unit of formula (3) is preferably 30 to 70% by mass, more preferably 35 to 70% by mass, and further preferably 40 to 70% by mass relative to the total amount of the raw materials of component a. When the amount of the polyester polyol having a structural unit of formula (3) is 30 to 70% by mass relative to the total amount of the raw materials of component a, the elastic modulus of the outer coating film described later will not become too low, and the cured film will not become too brittle, so that a balanced outer coating film can be obtained.

[0162] The preferred solid content concentration when manufacturing component a is 10 to 90% by mass, more preferably 15 to 70% by mass, and further preferably 20 to 60% by mass. In addition, when a solution having a solid content concentration of 20 to 60% by mass is used to manufacture the curable composition of the present embodiment described later, from the viewpoint of uniform dispersion, the solution viscosity of the component a solution is preferably, for example, 5000 to 1000000 mPa·s under the measurement conditions described in the Examples.

[0163] There is no particular restriction on the order of feeding the raw materials into the reactor when producing component a. For example, the compound of formula (4), the polyester polyol having the structural unit of formula (3), the carboxyl-containing diol, and, if necessary, the compound of formula (4), the polyol having the structure of formula (3) and the polyol other than the carboxyl-containing diol are first fed into the reactor and dissolved in a solvent. Then, the polyisocyanate compound is added dropwise at usually 20°C to 140°C, more preferably 60°C to 120°C, and then the components are reacted at 50°C to 160°C, more preferably 60°C to 150°C.

[0164] The molar ratio of the raw materials is adjusted according to the molecular weight and acid value of the target component a. The molecular weight of the target component a can also be adjusted by using a monohydroxy compound. That is, when the target number average molecular weight is reached (or when it is close to the target number average molecular weight), a monohydroxy compound can be added in order to cap the terminal isocyanate group and suppress the further increase of the number average molecular weight.

[0165] When a monohydroxy compound is used, there will be no problem even if the number of isocyanate groups in the polyisocyanate compound is less than, equal to or greater than the total number of hydroxyl groups in the raw material of component a obtained by combining the compound of formula (4), the polyester polyol having the structural unit of formula (3), and the polyol component other than the compound of formula (4) and the polyol having the structure of formula (3).

[0166] When the monohydroxy compound is used in an excessive amount, unreacted monohydroxy compound remains. As a result, the excess monohydroxy compound may be used as a part of the solvent as it is, or may be removed by distillation or the like.

[0167] In addition, in order to use a monoisocyanate compound as a raw material of component a, the number obtained by subtracting the number of isocyanate groups of the monoisocyanate compound from the number of isocyanate groups of all raw material components of component a (i.e., the total number of isocyanate groups of the polyisocyanate compound used as the raw material of component a) needs to be less than the total number of alcoholic hydroxyl groups of all raw material components of component a, so that the terminal of the polyurethane being manufactured before the monoisocyanate compound is used for the reaction becomes a hydroxyl group. At the moment when the reaction of the alcoholic hydroxyl groups of all raw material components of component a and the isocyanate groups of the polyisocyanate compound used in component a is almost completed, in order to react the hydroxyl groups remaining at the terminal of the polyurethane being manufactured with the monoisocyanate compound, the monoisocyanate compound is added dropwise to the solution of the carboxyl-containing polyurethane being manufactured at 30° C. to 150° C., more preferably 70° C. to 140° C., and then maintained at the same temperature to complete the reaction.

[0168] The number average molecular weight of component a obtained as described above is preferably 3000-50000, more preferably 5000-50000, and further preferably 5000-30000. When the number average molecular weight is in the range, the disconnection inhibition, flexibility and low warping of the cured film can be further improved. In addition, it can also be expected that flexibility, elongation and strength will not be damaged, and the solubility of component a in the solvent (i.e. component b) is also good, and even if dissolved, the viscosity will not become too high, and the physical property can be further improved. Thus, it is suitable when the curable composition of the present embodiment is used for the manufacture of a flexible wiring board covered with an outer coating film of the present embodiment described later.

[0169] The "number average molecular weight" referred to here refers to the number average molecular weight in terms of polystyrene measured by gel permeation chromatography (hereinafter referred to as GPC). It should be noted that, in this specification, unless otherwise specified, the measurement conditions of GPC are as follows.

[0170] Device name: HPLC unit HSS-2000 manufactured by JASCO Corporation

[0171] Column: Shodex column LF-804

[0172] Mobile phase: tetrahydrofuran

[0173] Flow rate: 1.0mL / min

[0174] Detector: RI-2031Plus manufactured by JASCO Corporation

[0175] Temperature: 40.0℃

[0176] Sample volume: Sample loop 100μL

[0177] Sample concentration: adjusted to about 0.1 mass %.

[0178] The acid value of component a is preferably 10 to 70 mgKOH / g, more preferably 15 to 50 mgKOH / g. When the acid value is 10 to 70 mgKOH / g, the reactivity of the compound having two or more epoxy groups in one molecule described later (i.e., component c) and other components contained in the curable composition of the present embodiment will not decrease, and the heat resistance of the cured product of the present embodiment described later will not decrease, and it will not become too hard and too brittle. In addition, it is easy to achieve a balance between the solvent resistance of the outer coating film described later and the warping of the flexible wiring board of the present embodiment described later. It should be noted that in this specification, the acid value of component a is the value of the acid value measured by the potentiometric titration method of JIS K0070.

[0179] The content of component a is preferably 60 to 99.9% by mass relative to the total amount of component a and component c (a / (a+c)). The lower limit of the content (a / (a+c)) is more preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and further preferably 93% by mass or more. In addition, the upper limit of the content (a / (a+c)) is more preferably 99.5% by mass or less, further preferably 99.3% by mass or less, and further preferably 99.0% by mass or less.

[0180] (ingredient b)

[0181] The solvent (component b) which is one of the essential components of the curable composition of the present embodiment is not particularly limited as long as it is a solvent that can dissolve component a, and is preferably a solvent having a boiling point of 150°C or more and 250°C or less at atmospheric pressure. In order to achieve a balance between the solubility of component a, the volatility of the solvent, etc., two or more solvents having a boiling point of 150°C or more and 250°C or less at atmospheric pressure may be used in combination, and this is preferred. It is more preferred to use a solvent having a boiling point of 170°C or more and less than 200°C at atmospheric pressure and a solvent having a boiling point of 200°C or more and 220°C or less at atmospheric pressure in combination.

[0182] Examples of the solvent having a boiling point of 170° C. or higher and lower than 200° C. under atmospheric pressure include diethylene glycol diethyl ether (boiling point 189° C.), diethylene glycol ethyl methyl ether (boiling point 176° C.), dipropylene glycol dimethyl ether (boiling point 171° C.), 3-methoxybutyl acetate (boiling point 171° C.), and ethylene glycol monobutyl ether acetate (boiling point 192° C.).

[0183] In addition, examples of the solvent having a boiling point of 200°C to 220°C at atmospheric pressure include diethylene glycol butyl methyl ether (boiling point 212°C), tripropylene glycol dimethyl ether (boiling point 215°C), triethylene glycol dimethyl ether (boiling point 216°C), ethylene glycol dibutyl ether (boiling point 203°C), diethylene glycol monoethyl ether acetate (boiling point 217°C), diethylene glycol monoethyl ether acetate (boiling point 217°C), and γ-butyrolactone (boiling point 204°C).

[0184] From the viewpoint of being able to impart low-temperature curing properties due to high volatility and being able to efficiently carry out the production reaction of component a in a uniform system, it is preferred to combine at least one selected from diethylene glycol diethyl ether (boiling point 189° C.), diethylene glycol ethyl methyl ether (boiling point 176° C.) and dipropylene glycol dimethyl ether (boiling point 171° C.) as a solvent having a boiling point of 170° C. to 200° C. at atmospheric pressure with at least one selected from diethylene glycol monoethyl ether acetate (boiling point 217° C.) and γ-butyrolactone (boiling point 204° C.) as a solvent having a boiling point of 200° C. to 220° C. at atmospheric pressure. A more preferred combination is diethylene glycol diethyl ether (boiling point 189°C), which is a solvent having a boiling point of 170°C to less than 200°C under atmospheric pressure, and diethylene glycol monoethyl ether acetate (boiling point 217°C) and γ-butyrolactone (boiling point 204°C), which are solvents having a boiling point of 200°C to 220°C under atmospheric pressure.

[0185] When these preferred solvents are used in combination, they have low hygroscopicity, high boiling point, and low volatility, and are therefore excellent as solvents for screen printing inks.

[0186] In order to fully exhibit the above effect, the ratio of the solvent having a boiling point of 170° C. or higher and lower than 200° C. under atmospheric pressure to the solvent having a boiling point of 200° C. or higher and lower than 220° C. under atmospheric pressure is preferably in the range of 5:95 to 80:20, more preferably in the range of 10:90 to 60:40, in terms of mass ratio.

[0187] In addition, as a part of these preferred solvents, the synthesis solvent used in producing the component a can be directly used as a part of the solvent of the curable composition of the present embodiment, which is preferable in terms of process.

[0188] Furthermore, a solvent other than a solvent having a boiling point of 170° C. to less than 200° C. at atmospheric pressure and a solvent having a boiling point of 200° C. to 220° C. at atmospheric pressure may be used in combination within a range that does not impair the solubility of component a. A reactive monomer or a reactive diluent may also be used as a solvent.

[0189] The content of component b in the curable composition of the present embodiment is preferably 25 to 75% by mass, more preferably 35 to 70% by mass, and still more preferably 35 to 65% by mass, relative to the total amount of component a, component b, component c and component f as components of the curable composition of the present embodiment (wherein, when component f is not included in the curable composition of the present embodiment, it is the total amount of component a, component b and component c). If the content of component b is in the range of 25 to 75% by mass relative to the total amount of component a, component b, component c and component f as components of the curable composition of the present embodiment (wherein, when component f is not included in the curable composition of the present embodiment, it is the total amount of component a, component b and component c), the viscosity of the curable composition is good for printing by screen printing, and the spread of the curable composition due to bleeding after screen printing does not become so large, so as a result, the actual printing area of ​​the curable composition does not become too large compared to the portion to be applied with the curable composition (that is, the shape of the printing plate), which is preferred.

[0190] (ingredient c)

[0191] Component c, which is an essential component of the curable composition of the present embodiment, is not particularly limited as long as it is a compound having two or more epoxy groups in one molecule, and functions as a curing agent in the curable composition of the present embodiment.

[0192] Examples of the compound having two or more epoxy groups in one molecule include phenol novolac epoxy resins and o-cresol novolac epoxy resins; novolac epoxy resins obtained by epoxidizing phenols such as phenol, cresol, xylenol, resorcinol, catechol and / or naphthols such as α-naphthol, β-naphthol and dihydroxynaphthalene with a compound having an aldehyde group such as formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde and salicylaldehyde under an acidic catalyst; bisphenol A, bisphenol F, bisphenol S, alkyl-substituted or unsubstituted biphenols, stilbene; diglycidyl ethers of phenols (bisphenol A epoxy compounds, bisphenol F epoxy compounds, bisphenol S epoxy compounds, biphenyl epoxy compounds, stilbene epoxy compounds); glycidyl ethers of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; glycidyl ester epoxy resins of carboxylic acids such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid; glycidyl or methylglycidyl epoxy resins such as compounds in which the active hydrogen bonded to the nitrogen atom is replaced by a glycidyl group such as aniline, bis(4-aminophenyl)methane, and isocyanuric acid; aminophenyls such as p-aminophenol Glycidyl or methylglycidyl epoxy resins such as compounds in which the active hydrogen bonded to the nitrogen atom of a phenol or the active hydrogen of a phenolic hydroxyl group is replaced by a glycidyl group; alicyclic epoxy resins such as vinylcyclohexene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane obtained by epoxidizing an olefin bond in a molecule; glycidyl ethers of p-xylene and / or m-xylene-modified phenolic resins; glycidyl ethers of terpene-modified phenolic resins ethers; glycidyl ethers of dicyclopentadiene-modified phenolic resins; glycidyl ethers of cyclopentadiene-modified phenolic resins; glycidyl ethers of polycyclic aromatic ring-modified phenolic resins; glycidyl ethers of naphthalene-containing phenolic resins; halogenated phenol novolac-type epoxy resins; hydroquinone-type epoxy resins; trimethylolpropane-type epoxy resins; chain aliphatic epoxy resins obtained by oxidizing olefin bonds with peracids such as peracetic acid; diphenylmethane-type epoxy resins; epoxides of aralkyl-type phenolic resins such as phenol aralkyl resins and naphthol aralkyl resins; epoxy resins containing sulfur atoms; tricyclic [5.2.1.0 2.6 ] diglycidyl ether of decanedimethanol; epoxy resins having adamantane structures such as 1,3-bis(1-adamantyl)-4,6-bis(glycidyl)benzene, 1-[2',4'-bis(glycidyl)phenyl]adamantane, 1,3-bis(4'-glycidylphenyl)adamantane and 1,3-bis[2',4'-bis(glycidyl)phenyl]adamantane. Among them, from the perspective of being fluorine-free, especially halogen-free, component c preferably does not contain fluorine atoms, and more preferably does not contain halogen atoms.

[0193] Among them, compounds having two or more epoxy groups in one molecule and having an aromatic ring structure and / or an alicyclic structure are preferred.

[0194] From the viewpoint of further improving the physical properties of the cured product of the present embodiment described later, among the compounds having two or more epoxy groups in one molecule and having an aromatic ring structure and / or an alicyclic structure, the glycidyl ether of dicyclopentadiene-modified phenolic resin (i.e., having a tricyclic [5.2.1.0 2.6 ] decane structure and an aromatic ring structure and having two or more epoxy groups), epoxy resins having an adamantane structure such as 1,3-bis(1-adamantyl)-4,6-bis(glycidyl)benzene, 1-[2',4'-bis(glycidyl)phenyl]adamantane, 1,3-bis(4'-glycidylphenyl)adamantane and 1,3-bis[2',4'-bis(glycidyl)phenyl]adamantane (i.e., having a tricyclic [3.3.1.1 3.7 ] Compounds having a tricyclodecane structure and an aromatic ring structure and having two or more epoxy groups, such as a compound having a decane structure and an aromatic ring structure and having two or more epoxy groups, are preferred because they can provide a cured product with low water absorption, and more preferred is the compound of the following formula (5).

[0195] [Chemical formula 24]

[0196]

[0197] (The l in the formula represents a natural number.)

[0198] Furthermore, when emphasis is placed on the reactivity with component a, among the compounds having two or more epoxy groups in one molecule and having an aromatic ring structure and / or an alicyclic structure, preferred are compounds having an amino group and an aromatic ring structure and having two or more epoxy groups, such as glycidyl or methylglycidyl epoxy resins such as aniline and bis(4-aminophenyl)methane in which the active hydrogen bonded to the nitrogen atom is substituted with a glycidyl group, and glycidyl or methylglycidyl epoxy resins such as p-aminophenol in which the active hydrogen bonded to the nitrogen atom and the active hydrogen of the phenolic hydroxyl group are substituted with a glycidyl group. More preferred are compounds of the following formula (6).

[0199] [Chemical formula 25]

[0200]

[0201] Component c may be used alone or in combination of two or more.

[0202] The amount of component c to be added relative to 100 parts by mass of component a, which is an essential component of the curable composition of this embodiment, varies depending on the number of functional groups including carboxyl groups in component a that are reactive with epoxy groups, and therefore cannot be determined in general.

[0203] Among them, the ratio of the number of functional groups containing carboxyl groups that can react with epoxy groups contained in component a to the number of epoxy groups in component c (compounds having two or more epoxy groups in one molecule) (functional groups that can react with epoxy groups / epoxy groups) is preferably in the range of 1 / 3 to 2 / 1, and more preferably in the range of 1 / 2.5 to 1.5 / 1. When the ratio is in the range of 1 / 3 to 2 / 1, when the curable composition of the present embodiment is cured, unreacted component c will not remain in large quantities, and functional groups containing carboxyl groups that can react with epoxy groups will not remain so much, and functional groups containing carboxyl groups that can react with epoxy groups can react with epoxy groups in component c (compounds having two or more epoxy groups in one molecule) in a well-balanced manner.

[0204] In addition, the amount of component c in the curable composition of the present embodiment is preferably 1 to 60% by mass, more preferably 2 to 50% by mass, and further preferably 3 to 40% by mass relative to the total amount of component a and component c in the curable composition. When the amount of component c in the curable composition of the present embodiment is in the range of 1 to 60% by mass relative to the total amount of component a and component c in the curable composition, a balance can be achieved between the solvent resistance of the outer coating film of the present embodiment described later, the low warpage of the flexible wiring board covered by the outer coating film, and the disconnection suppression effect.

[0205] (ingredient d)

[0206] Component d is the first defoamer containing olefins. It should be noted that, in this specification, the term "olefin" includes olefins, olefin polymers, and compounds formed by chemically modifying them, and the term "olefins" includes olefins themselves and mixtures with olefins as components. In addition, the term "olefin polymer" includes homopolymers and copolymers. As a specific example of component d, for example, a defoamer containing olefin polymers (such as olefin oligomers, olefin polymers, etc.) can be cited. Component d can use so-called olefin defoamers, or commercial products can be used. As such a specific example, for example, BYK-1791 (manufactured by BYK-CHEM IE JAPAN Co., Ltd.), FLOWLEN AC-2000HF (manufactured by Kyoeisha Chemical Co., Ltd.), FLOWLENAC-2200HF (manufactured by Kyoeisha Chemical Co., Ltd.), DISPARLON P-465 (manufactured by Kusumoto Chemicals Co., Ltd.), DISPARLONP-466 (manufactured by Kusumoto Chemicals Co., Ltd.), etc. can be cited.

[0207] When the curable composition of the present embodiment is used as an anti-corrosion ink composition for insulating protection of wiring (i.e., an outer coating agent for wiring boards), a defoaming agent can be used, and is preferably used, for the purpose of eliminating bubbles during printing (defoaming), suppressing the generation of bubbles (foam suppression), and removing bubbles in the liquid (defoaming).

[0208] In the curable composition of this embodiment, by adding at least component d as a defoaming agent relative to the composition of components a, b and c, unexpectedly, the physical properties of the cured product are excellent compared to defoaming agents containing fluorine compounds, etc., and defoaming effects such as defoaming, foam suppression and degassing can be maintained.

[0209] (ingredient e)

[0210] The curable composition of the present embodiment may contain the following component e, and preferably contains the following component e. In the curable composition of the present embodiment, by using component e as a defoaming agent in addition to component d in the composition of the components a, b, and c, the above effect can be expected to be further improved.

[0211] Component e is a second defoamer comprising an acrylic resin and / or a methacrylic resin. The acrylic resin referred to herein refers to a resin having an acrylic skeleton, and the methacrylic resin refers to a resin having a methacrylic skeleton. Component e may use a so-called acrylic defoamer or a methacrylic defoamer, or a commercially available product. Specific examples thereof include acrylic polymer defoaming agents such as DAPPOSN-348 (manufactured by Sannopco Co., Ltd.), DAPPOSN-354 (manufactured by Sannopco Co., Ltd.), DAPPOSN-368 (manufactured by Sannopco Co., Ltd.), DISPARLON 230HF (manufactured by Kusumoto Chemicals Co., Ltd.), BYK-361 (manufactured by BYK-CHEMIE JAPAN Co., Ltd.), BYK-381 (manufactured by BYK-CHEMIE JAPAN Co., Ltd.), BYK-394 (manufactured by BYK-CHEMIE JAPAN Co., Ltd.), POLYFLOW 36 (manufactured by Kyoeisha Chemical Co., Ltd.), POLYFLOW 75 (manufactured by Kyoeisha Chemical Co., Ltd.), and POLYFLOW 77 (manufactured by Kyoeisha Chemical Co., Ltd.). It should be noted that the curable composition of the present embodiment can obtain a practical level of effect even if only component e is used as a defoamer. In addition, the curable composition of the present embodiment can also improve its effect to a higher level by using component e and component d in combination as a defoamer. In addition, the curable composition of the present embodiment can also obtain a fully excellent effect by using only component e and component d as a defoamer.

[0212] (Other defoamers)

[0213] The curable composition of the present embodiment can fully obtain the desired effect even if it does not contain a defoamer other than the above-mentioned component d and component e, and may contain a defoamer other than the component d and component e (third defoamer) as needed. Specific examples of such a third defoamer include: polysiloxane defoamers such as BYK-333 (manufactured by BYK-CHEMIE JAPAN Co., Ltd.), BYK-342 (manufactured by BYK-CHEMIE JAPAN Co., Ltd.), SN DEFOAMER 470 (manufactured by SAN NOPCO Co., Ltd.), TSA750S (manufactured by Momentive Performance Materials Co., Ltd.), silicone oil SH-203 (manufactured by Dupont Toray Specialty Materials Co., Ltd.), acetylene glycol defoamers such as SURFYNOL DF-110D (manufactured by Nissin Chemical Industry Co., Ltd.), and SURFYNOL DF-37 (manufactured by Nissin Chemical Industry Co., Ltd.). Among them, from the viewpoint of preparing a fluorine-free curable composition containing no fluorine atoms, the curable composition of the present embodiment preferably does not contain a fluorine-containing polysiloxane defoamer, etc. In addition, from the viewpoint of not containing polysiloxane, the curable composition of the present embodiment preferably does not contain a defoamer containing polysiloxane-containing materials such as polysiloxane (polysiloxane defoamer).

[0214] Regarding the content of the defoamer, the total amount (d+e) of component d and component e in the curable composition of the present embodiment is preferably 0.01 to 3% by mass. The lower limit of the content is more preferably 0.1% by mass or more, more preferably 0.3% by mass or more, more preferably 0.5% by mass or more, and more preferably 0.6% by mass or more. In addition, the upper limit of the content is more preferably 2.5% by mass or less, more preferably 2.0% by mass or less, more preferably 1.5% by mass or less, and more preferably 1.3% by mass or less.

[0215] In addition, regarding the content of the defoamer, when the total amount of the components after removing the content of component b from the total amount of the curable composition of the present embodiment is set to 100% by mass, the total amount of component d and component e is preferably 0.01 to 5% by mass. Its lower limit is more preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 1.5% by mass or more, more preferably 1.7% by mass or more, and more preferably 2% by mass or more. In addition, its upper limit is more preferably 4% by mass or less, more preferably 3.5% by mass or less, and more preferably 3% by mass or less.

[0216] The content of the defoaming agent is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 4 parts by mass, and even more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the total amount of component a, component b, component c, and component f.

[0217] Component e is preferably 1 to 150% by mass relative to component d (e / d). Its lower limit is more preferably 3% by mass or more, more preferably 5% by mass or more, and more preferably 7% by mass or more. In addition, its upper limit is more preferably 120% by mass or less, more preferably 100% by mass or less, more preferably 60% by mass or less, more preferably 30% by mass or less, more preferably 17% by mass or less, more preferably 15% by mass or less, and more preferably 13% by mass or less. By setting the proportion of component d to component e as the mass ratio, the balance of wire breakage inhibition, low warpage, flexibility and defoaming properties can be improved to a higher level.

[0218] (ingredient f)

[0219] The curable composition of the present embodiment may contain the following component f, and preferably contains the following component f.

[0220] Component f is at least one type of fine particles selected from inorganic fine particles and organic fine particles.

[0221] Examples of inorganic fine particles include silicon dioxide (SiO2), aluminum oxide (Al2O3), titanium dioxide (TiO2), tantalum oxide (Ta2O5), zirconium oxide (ZrO2), silicon nitride (Si3N4), barium titanate (BaO·TiO2), barium carbonate (BaCO3), lead titanate (PbO·TiO2), lead zirconate titanate (PZT), lead lanthanum zirconate titanate (PLZT), gallium oxide (Ga2O3), spinel (MgO·Al2O3), mullite (3Al2O3·2SiO2), cordierite (2MgO·2Al2O3·5SiO2), talc (3MgO·4SiO2·H2O), aluminum titanate (TiO2-Al2O3), yttria-containing zirconium oxide (Y2O3-ZrO2), barium silicate (BaO·8SiO2), boron nitride (BN), calcium carbonate (CaCO3), calcium sulfate (CaSO4), and the like. SO4), zinc oxide (ZnO), magnesium titanate (MgO·TiO2), barium sulfate (BaSO4), organic bentonite, carbon (C), hydrotalcite, etc.

[0222] As organic microparticles, microparticles of heat-resistant resins having amide bonds, imide bonds, ester bonds or ether bonds are preferred. As these resins, from the viewpoint of heat resistance and mechanical properties, polyimide resins or their precursors, polyamideimide resins or their precursors, or polyamide resins are preferably cited.

[0223] As the component f, one kind thereof may be used alone, or two or more kinds thereof may be used in combination.

[0224] Among these, component f preferably contains at least one selected from silica particles and hydrotalcite particles. That is, component f preferably contains silica particles. In addition, component f preferably contains hydrotalcite particles. As component f, both silica particles and hydrotalcite particles may be contained.

[0225] The silica particles used in the curable composition of the present embodiment are defined as particles that are physically coated in powder form or chemically surface-treated with an organic compound. The silica particles used in the curable composition of the present embodiment are not particularly limited as long as they are silica particles dispersed in the curable composition of the present embodiment to form a paste, and examples thereof include AEROSIL provided by AEROSIL Co., Ltd. of Japan. These silica particles, exemplified by AEROSIL, are sometimes also used to impart printability during screen printing, in which case they are used for the purpose of imparting thixotropy.

[0226] The hydrotalcite particles used in the curable composition of this embodiment are Mg6Al2(OH) 16 A type of naturally occurring clay mineral represented by CO3·4H2O, etc., which is a layered inorganic compound. Alternatively, hydrotalcite can also be synthesized by, for example, Mg (1-x) Al x (OH)2(CO3) x / 2 That is, hydrotalcite is a Mg / Al-based layered compound that can fix chloride ions (Cl - ) and / or sulfate ions (SO4 - ) anions. This function is used to capture chloride ions (Cl - ), sulfate ion (SO4 - ), can be used for the purpose of improving insulation reliability.

[0227] Examples of commercially available hydrotalcites include STABIACE HT-1, STABIACE HT-7, and STABIACE HT-P manufactured by Sakai Chemical Co., Ltd., and DHT-4A, DHT-4A-2, and DHT-4C manufactured by Kyowa Chemical Industry Co., Ltd.

[0228] The average particle size of these inorganic fine particles and / or organic fine particles is preferably 0.01 to 10 μm, more preferably 0.1 to 5 μm.

[0229] In addition, the amount of component f is preferably 0.1 to 60% by mass, more preferably 0.3 to 55% by mass, and further preferably 0.5 to 40% by mass relative to the total amount of component a, component b, component c, and component f. If the amount of component f is in the range of 0.1 to 60% by mass relative to the total amount of component a, component b, component c, and component f, the viscosity of the curable composition is good for printing by screen printing, and the expansion of the curable composition after screen printing caused by bleeding will not become so large, so as a result, compared with the part to be applied with the curable composition (i.e., the shape of the printing plate), the actual printing area of ​​the curable composition will not become too large, so it is preferred.

[0230] (Curing accelerator)

[0231] The curable composition of the present embodiment may further include a curing accelerator, and is preferred. As a curing accelerator, there is no particular limitation as long as it is a compound that promotes the reaction of the epoxy group of component c with the carboxyl group of component a. As a curing accelerator, for example, triazine compounds such as melamine, methylguanamine, benzoguanamine, 2,4-diamino-6-methacryloyloxyethyl-s-triazine, 2,4-methacryloyloxyethyl-s-triazine, 2,4-diamino-6-vinyl-s-triazine, 2,4-diamino-6-vinyl-s-triazine · isocyanuric acid adduct, imidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1-benzyl-2-methylimidazole, 2-phenyl-4-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-aminoethyl 1-(cyanoethylaminoethyl)-2-methylimidazole, N-[2-(2-methyl-1-imidazolyl)ethyl]urea, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-methylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 1-cyanoethyl-2-ethyl-4-methylimidazolium trimellitate, 1-cyanoethyl-2-undecylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1 ')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, N,N'-bis(2-methyl-1-imidazolylethyl)urea, N,N'-bis(2-methyl-1-imidazolylethyl)adipamide, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-methylimidazole·isocyanuric acid adduct, 2-phenylimidazole·isocyanuric acid adduct, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine·isocyanuric acid adduct, 2-methyl-4- imidazole compounds such as formyl imidazole, 2-ethyl-4-methyl-5-formyl imidazole, 2-phenyl-4-methyl formyl imidazole, 1-benzyl-2-phenyl imidazole, 1,2-dimethyl imidazole, 1-(2-hydroxyethyl) imidazole, vinyl imidazole, 1-methyl imidazole, 1-allylimidazole, 2-ethyl imidazole, 2-butyl imidazole, 2-butyl-5-hydroxymethyl imidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-benzyl-2-phenyl imidazole hydrogen bromide, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 1,5-diazabicyclo(4.3.0)nonene-5 and its salts, 1,8-diazabicyclo(5.4.0) Cyclic amidine compounds and derivatives thereof such as diazabicycloolefins such as undecene-7 and its salts, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, tris(dimethylaminomethyl)phenol and other tertiary amino group-containing compounds, triphenylphosphine, diphenyl(p-tolyl)phosphine, tri(alkylphenyl)phosphine, tri(alkoxyphenyl)phosphine, tri(alkyl-alkoxyphenyl)phosphine, tri(dialkylphenyl)phosphine, tri(trialkylphenyl)phosphine, tri(tetraalkylphenyl)phosphine, tri(dialkoxyphenyl)phosphine, tri(trialkoxyphenyl)phosphine, tri(tetraalkoxyphenyl)phosphine, trialkylphosphine, dialkylarylphosphine, alkyldiarylphosphine and other organic phosphine compounds, dicyandiamide, etc.

[0232] These curing accelerators may be used alone or in combination of two or more.

[0233] Among these curing accelerators, if the curing accelerating effect and the electrical insulation performance of the cured product of the present embodiment described later are taken into consideration, the preferred curing accelerators are melamine, imidazole compounds, cyclic amidine compounds and their derivatives, phosphine compounds and amine compounds, and more preferably melamine, 1,5-diazabicyclo (4.3.0) nonene-5 and its salts, 1,8-diazabicyclo (5.4.0) undecene-7 and its salts.

[0234] The amount of these curing accelerators is not particularly limited as long as the curing acceleration effect can be achieved. Among them, from the perspective of the curability of the curable composition of the present embodiment and the electrical insulation properties and water resistance of the cured product of the present embodiment described later, relative to the total amount of 100 parts by mass of component a and component c, the curing accelerator is preferably mixed in the range of 0.05 to 5 parts by mass, and more preferably in the range of 0.1 to 3.0 parts by mass. When the amount is in the range of 0.05 to 5 parts by mass, the curable composition of the present embodiment can be cured in a short time, and the electrical insulation properties and water resistance of the cured product obtained by curing the composition of the present embodiment described later are good.

[0235] (Other ingredients)

[0236] When the curable composition of the present embodiment is cured, a cured product having excellent electrical insulating properties can be obtained. Therefore, the curable composition can be used as a composition for use in, for example, resist ink for insulation protection of wiring.

[0237] Furthermore, the curable composition of the present embodiment may contain surfactants such as a leveling agent, and known colorants such as phthalocyanine blue, phthalocyanine green, iodine green, disazo yellow, crystal violet, carbon black, and naphthalene black, as needed.

[0238] Furthermore, when it is necessary to suppress oxidative degradation of component a and discoloration during heating, antioxidants such as phenolic antioxidants, phosphite antioxidants, and thioether antioxidants may be added, and are preferred.

[0239] Furthermore, a flame retardant or a lubricant may be added as necessary.

[0240] The curable composition of the present embodiment can be obtained by uniformly kneading and mixing a part or all of the ingredients using a roll mill, a bead mill, etc. When a part of the ingredients are mixed, the remaining ingredients can be mixed in actual use.

[0241] (Viscosity of the curable composition of the present embodiment)

[0242] The curable composition of the present embodiment has excellent operability and can maintain the physical properties such as the wire breaking inhibition, low warping, flexibility and defoaming at an excellent level. From such a viewpoint, the viscosity of the curable composition of the present embodiment at 25°C can be preferably set to 10000-100000 mPa·s. In addition, the lower limit of the viscosity is more preferably 20000 mPa·s or more, more preferably 23000 mPa·s or more, and more preferably 25000 mPa·s or more. In addition, the upper limit of the viscosity is more preferably 60000 mPa·s or less, more preferably 50000 mPa·s or less, and more preferably 45000 mPa·s or less. It should be noted that in this specification, the viscosity of the curable composition of the present embodiment at 25°C is the viscosity measured after 7 minutes from the start of rotation using a cone / plate viscometer (Brookfield, model: DV-II+Pro, spindle model: CPE-52) at a rotation speed of 10 rpm.

[0243] (Thixotropic Index of Curable Composition of the Present Embodiment)

[0244] When the curable composition of the present embodiment is used as a resist ink composition for insulating wiring (i.e., an overcoat for wiring boards), etc., the thixotropic index of the composition is preferably within a certain range in order to improve the printability of the curable composition of the present embodiment.

[0245] It should be noted that the "thixotropic index" described in this specification is defined as the ratio of the viscosity at a rotation speed of 1 rpm at 25°C to the viscosity at a rotation speed of 10 rpm at 25°C (viscosity at 1 rpm / viscosity at 10 rpm), measured using a cone / plate viscometer (manufactured by Brookfield, model: DV-III+Pro, spindle model: CPE-52).

[0246] When the curable composition of the present embodiment is used as an outer coating agent for wiring boards, in order to make the printability of the curable composition of the present embodiment good, the thixotropic index of the composition is preferably 1.1 or more, more preferably in the range of 1.1 to 3.0, and further preferably in the range of 1.1 to 2.5. When the curable composition of the present embodiment is used as an outer coating agent for wiring boards, if the thixotropic index of the curable composition is 1.1 to 3.0, after printing the curable composition, the composition can have a certain film thickness, the printed pattern can be maintained, and the defoaming property of the printed film of the composition after printing also becomes good.

[0247] <Cured product and outer coating film for flexible wiring board>

[0248] The curable composition can be cured and used suitably as a cured product. That is, the cured product of the present embodiment is a cured product obtained by curing the curable composition.

[0249] Furthermore, the cured product can be suitably used for an outer coating film for a flexible wiring board, etc. That is, the outer coating film for a flexible wiring board of the present embodiment is an outer coating film for a flexible wiring board including the cured product.

[0250] The cured product of the present embodiment and the outer coating of the present embodiment can be obtained, for example, by heating the curable composition of the present embodiment to allow the curing reaction to proceed. The method for obtaining the cured product of the present embodiment as a cured film is not particularly limited, and for example, a cured film or an outer coating can be obtained by the following steps.

[0251] (First step) a step of printing the curable composition of the present embodiment on a substrate or the like to obtain a printed film;

[0252] (Second step) A step of heat-curing the printed film obtained in the first step, or a printed film from which a part or all of the solvent is removed by placing the printed film obtained in the first step in an atmosphere of 40°C to 100°C to evaporate a part or all of the solvent in the printed film, in an atmosphere of 100°C to 170°C to obtain a cured film or an outer coating film.

[0253] The method for printing the curable composition of the present embodiment in the first step is not particularly limited, and for example, the curable composition may be applied to a substrate or the like by screen printing, roll coating, spraying, curtain coating, or the like to obtain a printed film.

[0254] The operation of evaporating the solvent in the second step is an operation performed as needed. The operation of heat curing can be performed immediately after the operation of the first step, and the curing reaction and the removal of the solvent can be performed together. In the case of performing the operation of evaporating the solvent before heat curing in the second step, the temperature is usually 40°C to 100°C, preferably 60°C to 100°C, and more preferably 70°C to 90°C, considering the evaporation rate of the solvent and the rapid transfer to the heat curing step. The time for evaporating the solvent in the second step is not particularly limited, but is preferably 10 minutes to 120 minutes, and more preferably 20 minutes to 100 minutes.

[0255] The temperature of the heat curing performed in the second step is preferably in the range of 100° C. to 170° C., more preferably 105° C. to 160° C., and further preferably 110° C. to 150° C. The time of the heat curing performed in the second step is not particularly limited, but is preferably in the range of 20 minutes to 240 minutes, and more preferably in the range of 30 minutes to 120 minutes.

[0256] <Flexible wiring board and method for manufacturing flexible wiring board>

[0257] The flexible wiring board of the present embodiment and the manufacturing method of the flexible wiring board of the present embodiment are described. The curable composition of the present embodiment can be used as an insulating protective ink for wiring, and the cured product of the present embodiment can be used as an insulating protective film. In particular, it can be used as an insulating protective resist for wiring by covering all or part of the wiring of a flexible wiring board such as a chip on film.

[0258] The present embodiment is a flexible wiring board formed by forming wiring on a flexible substrate, and a part or all of the surface on which the wiring is formed is covered with a cured product of the present embodiment (e.g., an outer coating film for the flexible wiring board, etc.) It should be noted that, considering the anti-oxidation and economic aspects of the wiring, the wiring covered by the cured product of the present embodiment is preferably a tinned copper wiring.

[0259] The manufacturing method of the present embodiment is a manufacturing method of a flexible wiring board covered with a protective film, wherein the curable composition of the present embodiment is printed on at least a part of the wiring pattern portion of the flexible wiring board to form a printed film on the pattern, and the printed film is cured by heating at 100° C. to 170° C. to form a protective film. For example, the protective film of the flexible wiring board can be formed by going through the following steps A to C.

[0260] (Step A) A step of printing the curable composition of the present embodiment on at least a part of the wiring pattern portion of a flexible wiring board to form a printed film on the pattern.

[0261] (Step B) A step of evaporating part or all of the solvent in the printed film by placing the printed film obtained in the step A in an atmosphere of 40° C. to 100° C.

[0262] (Step C) A step of curing the printed film obtained in the step A or the printed film obtained in the step B by heating at 100° C. to 170° C. to form a protective film for a flexible wiring board.

[0263] This embodiment is more preferably a method for producing a flexible wiring board covered with an overcoat film, comprising the following steps A to C.

[0264] (Step A) a step of forming a printed film on a flexible wiring board having wiring formed on a flexible substrate by printing the curable composition of the present embodiment on a part or the entirety of the surface on which wiring is formed,

[0265] (Step B) a step of evaporating part or all of the solvent in the printed film by placing the printed film obtained in step A in an atmosphere of 40° C. to 100° C.,

[0266] (Step C) A step of curing the printed film obtained in the step A or the printed film obtained in the step B by heating at 100° C. to 170° C. to form an overcoat film.

[0267] The operation of evaporating the solvent in step B is an operation performed as needed, and the operation of thermal curing can be performed immediately after the operation of step A, so that the curing reaction and the removal of the solvent are performed together. In the case where the operation of evaporating the solvent is performed before thermal curing in step B, the temperature is usually 40° C. to 100° C., preferably 60° C. to 100° C., and more preferably 70° C. to 90° C., considering the evaporation rate of the solvent and the rapid transfer to the thermal curing step. The time for evaporating the solvent in step B is not particularly limited, but is preferably 10 minutes to 120 minutes, and more preferably 20 minutes to 100 minutes.

[0268] The conditions for the heat curing performed in step C are in the range of 100° C. to 170° C. from the viewpoint of diffusing the plating layer and obtaining low warpage, flexibility, and softness suitable as a protective film. The heat curing temperature is preferably 105° C. to 160° C., and more preferably 110° C. to 150° C. The heat curing time performed in step C is not particularly limited, but is preferably 10 minutes to 150 minutes, and more preferably 15 minutes to 120 minutes.

[0269] As described above, the curable composition of the present embodiment is excellent in disconnection inhibition, low warpage and flexibility when it is made into a cured product. Therefore, when the curable composition of the present embodiment is applied to a flexible substrate such as a flexible wiring board or a polyimide film, and then a cured product (protective film) is prepared by a curing reaction, the flexible wiring board with a protective film and the flexible substrate with a protective film have small warpage, and then the position alignment of the IC chip mounting process can be made easy. Therefore, the curable composition of the present embodiment can be suitable for forming an outer coating film for a flexible wiring board.

[0270] The curable composition of the present embodiment can also be expected to provide good workability. When a cured product is prepared, it can be expected to have good adhesion to a substrate, flexibility, moisture resistance, etc., and good electrical insulation reliability over a long period of time.

[0271] The cured product of this embodiment has at least excellent disconnection suppression performance and is expected to have good flexibility that contributes thereto, and is therefore suitable for providing a flexible wiring board with an electrically insulating protective film that is less prone to cracking (eg, a flexible printed wiring board such as COF).

[0272] Example

[0273] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0274] <Determination of Acid Value>

[0275] The solvent in the polyurethane solution used in the present embodiment is distilled off under reduced pressure while heating to obtain component a.

[0276] Using the component a obtained by the above method, the acid value was measured according to the potentiometric titration method of JIS K0070.

[0277] The apparatus used in the potentiometric titration method is described below.

[0278] Device name: Kyoto Electronics Co., Ltd. Potentiometric automatic titrator AT-510

[0279] Electrode: Composite glass electrode C-173 manufactured by Kyoto Electronics Industry Co., Ltd.

[0280] <Measurement of Number Average Molecular Weight of Component a>

[0281] The number average molecular weight is a polystyrene-equivalent number average molecular weight measured by GPC. The measurement conditions of GPC are as follows.

[0282] Device name: HPLC unit HSS-2000 manufactured by JASCO Corporation

[0283] Column: Shodex column LF-804

[0284] Mobile phase: tetrahydrofuran

[0285] Flow rate: 1.0mL / min

[0286] Detector: RI-2031Plus manufactured by JASCO Corporation

[0287] Temperature: 40.0℃

[0288] Sample volume: Sample loop 100μL

[0289] Sample concentration: adjusted to about 0.1 mass%

[0290] <Measurement of Viscosity of Solution Containing Component a>

[0291] The viscosity of the polyurethane solution was measured by the following method.

[0292] About 0.8 g of the polyurethane solution was used to measure the viscosity 7 minutes after the start of the measurement at a temperature of 25.0° C. and a rotation speed of 5 rpm using a cone / plate viscometer (Brookfield, model: DV-II+Pro, spindle model: CPE-52).

[0293] <Measurement of Viscosity of Curable Composition>

[0294] The viscosity of the curable composition was measured by the following method.

[0295] About 0.6 g of the curable composition was used to measure the viscosity 7 minutes after the start of the measurement at a temperature of 25.0° C. and a rotation speed of 10 rpm using a cone / plate viscometer (Brookfield, model: DV-II+Pro, spindle model: CPE-52).

[0296] <Synthesis of Polyester Polyol>

[0297] (Reference Synthesis Example 1)

[0298] In a reaction vessel equipped with a stirring device, a thermometer and a condenser with a distillation device, 983.5 g (6.74 mol) of phthalic anhydride and 879.2 g (7.44 mol) of 1,6-hexanediol were added, and the internal temperature of the reaction vessel was raised to 140°C using an oil bath, and stirring was continued for 4 hours. Then, while continuing to stir, 1.74 g of mono-n-butyltin oxide was added, the internal temperature of the reaction vessel was slowly raised, a vacuum pump was connected, and the pressure in the reaction vessel was reduced little by little, and water was removed from the reaction vessel by vacuum distillation. Finally, the internal temperature was raised to 220°C and the pressure was reduced to 133.32 Pa. After 15 hours, it was confirmed that water was no longer distilled away, and the reaction was terminated. The hydroxyl value of the obtained polyester polyol (hereinafter referred to as polyester diol (α)) was measured, and the result was 53.1 mg-KOH / g.

[0299] <Synthesis of Polyurethane>

[0300] (Implementation of Synthesis Example 1)

[0301] In a reaction container equipped with a stirrer, a thermometer and a condenser, 10.7 g (24.4 mmol, 97.6 mmol) of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemical Co., Ltd., trade name: BPEF), 61.52 g of P-2030 (manufactured by KURARAY Co., Ltd., a polyester polyol containing isophthalic acid / 3-methyl-1,5-pentanediol), 6.48 g of 2,2-dimethylolpropionic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a carboxyl group-containing diol, and 137.7 g of γ-butyrolactone as a solvent were added, and the mixture was heated to 100° C. to dissolve all the raw materials.

[0302] The temperature of the reaction solution was lowered to 90°C, and 28.31 g of methylenebis(4-cyclohexyl isocyanate) (manufactured by Sumika Bayer Urethane Co., Ltd., trade name: Desmodur-W) as a polyisocyanate compound was added dropwise using a dropping funnel over 30 minutes. The reaction was carried out at 145°C to 150°C for 8 hours, and after confirming by IR that the absorption of C=O stretching vibration derived from the isocyanate group was almost not observed, 1.5 g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) and 24.3 g of diethylene glycol diethyl ether (manufactured by Nippon Emulsifier Co., Ltd.) were added dropwise, and then the reaction was carried out at 80°C for 3 hours to obtain a solution containing a polyurethane having a carboxyl group and an aromatic ring concentration of 3.1 mmol / g (hereinafter referred to as "polyurethane solution A1").

[0303] The viscosity of the obtained polyurethane solution A1 was 120,000 mPa·s. The number average molecular weight of the polyurethane having carboxyl groups and an aromatic ring concentration of 3.1 mmol / g (hereinafter referred to as "polyurethane AU1") contained in the polyurethane solution A1 was 20,000, and the acid value of polyurethane AU1 was 25.0 mg-KOH / g.

[0304] The solid content concentration in the polyurethane solution A1 was 40.0% by mass.

[0305] (Implementation of Synthesis Example 2)

[0306] In a reaction container equipped with a stirring device, a thermometer and a condenser, 21.0 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemical Co., Ltd., trade name: BPEF), 66.7 g of the polyester diol (α) (polyester polyol containing phthalic acid / 1,6-hexanediol), 3.00 g of 2,2-dimethylolpropionic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a carboxyl group-containing diol, and 83.24 g of γ-butyrolactone as a solvent were charged, and the mixture was heated to 100° C. to dissolve all the raw materials.

[0307] The temperature of the reaction solution was lowered to 90°C, and a solution prepared by dissolving 26.50 g of diphenylmethane-4,4'-diisocyanate (manufactured by Tosoh Corporation, trade name: Millionate MT) in 60.0 g of γ-butyrolactone was added dropwise using a dropping funnel over 20 minutes. The reaction was carried out at 125°C to 130°C for 8 hours, and after confirming that the absorption of C=O stretching vibration derived from the isocyanate group was almost not observed by IR, 1.5 g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.), 6.19 g of γ-butyrolactone, and 26.37 g of diethylene glycol diethyl ether (manufactured by Nippon Emulsifier Co., Ltd.) were added dropwise, and then the reaction was carried out at 80°C for 3 hours to obtain a solution containing a polyurethane having a carboxyl group and an aromatic ring concentration of 5.6 mmol / g (hereinafter referred to as "polyurethane solution A2").

[0308] The viscosity of the obtained polyurethane solution A2 was 120,000 mPa·s. The number average molecular weight of the polyurethane having carboxyl groups and an aromatic ring concentration of 5.6 mmol / g (hereinafter referred to as "polyurethane AU2") contained in the polyurethane solution A2 was 20,000, and the acid value of polyurethane AU2 was 10.6 mg-KOH / g.

[0309] The solid content concentration in the polyurethane solution A2 was 40.0% by mass.

[0310] (Implementation of Synthesis Example 3)

[0311] In a reaction container equipped with a stirrer, a thermometer and a condenser, 5.0 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemical Co., Ltd., trade name: BPEF), 73.00 g of polycarbonate diol (polyester polyol containing 3-methyl-1,5-pentanediol / 1,6-hexanediol, trade name: KURARAY POLYOL C-2090, hydroxyl value: 1955), 6.75 g of 2,2-dimethylolpropionic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a carboxyl group-containing diol, and 136.34 g of γ-butyrolactone as a solvent were charged, and the mixture was heated to 100° C. to dissolve all the raw materials.

[0312] The temperature of the reaction solution was lowered to 90°C, and 26.80 g of methylenebis(4-cyclohexyl isocyanate) (manufactured by Sumikabayer Urethane Co., Ltd., trade name: Desmodur-W) as a polyisocyanate compound was added dropwise using a dropping funnel over 30 minutes. The reaction was carried out at 145°C to 150°C for 10 hours, and after confirming by IR that the absorption of C=O stretching vibration derived from the isocyanate group was almost not observed, 1.5 g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.), 5.89 g of γ-butyrolactone, and 25.10 g of diethylene glycol diethyl ether (manufactured by Nippon Emulsifier Co., Ltd.) were added dropwise, and then the reaction was carried out at 80°C for 3 hours to obtain a solution containing a polyurethane having a carboxyl group and an aromatic ring concentration of 0.4 mmol / g (hereinafter referred to as "polyurethane solution A3").

[0313] The viscosity of the obtained polyurethane solution A3 was 120,000 mPa·s. The number average molecular weight of the polyurethane having carboxyl groups and an aromatic ring concentration of 0.4 mmol / g (hereinafter referred to as "polyurethane AU3") contained in the polyurethane solution A3 was 20,000, and the acid value of polyurethane AU3 was 25.0 mg-KOH / g.

[0314] The solid content concentration in the polyurethane solution A3 was 40.0% by mass.

[0315] (Comparative Synthesis Example 1)

[0316] In a reaction container equipped with a stirring device, a thermometer and a condenser, 248.0 g of C-1090 (manufactured by KURARAY Co., Ltd., a (poly)carbonate diol made of 1,6-hexanediol and 3-methyl-1,5-pentanediol, hydroxyl value 122.22 mg-KOH / g) as a (poly)carbonate polyol, 47.5 g of 2,2-dimethylolbutyric acid (manufactured by Nippon Chemical Co., Ltd.) as a carboxyl group-containing diol, 2.7 g of trimethylolethane (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a polyol other than the (poly)carbonate polyol and the carboxyl group-containing diol, 467.5 g of γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) and 82.5 g of diethylene glycol diethyl ether (manufactured by Nippon Emulsifier Co., Ltd.) were charged, and the mixture was heated to 100° C. to dissolve all the raw materials.

[0317] The temperature of the reaction liquid was lowered to 90°C, and 150.4 g of methylenebis(4-cyclohexyl isocyanate) (manufactured by Sumikabayer Urethane Co., Ltd., trade name: Desmodur-W) as a diisocyanate compound was added dropwise using a dropping funnel over 30 minutes.

[0318] The reaction was carried out at 120°C for 8 hours, and it was confirmed by IR that the absorption of C=O stretching vibration derived from the isocyanate group was almost not observed. Then, 1.5 g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) was added dropwise to the reaction solution, and then the reaction was carried out at 80°C for 3 hours to obtain a polyurethane solution having a carboxyl group and a carbonate bond (hereinafter referred to as "polyurethane solution B1").

[0319] The viscosity of the obtained polyurethane solution B1 was 145000 mPa·s. The number average molecular weight of the polyurethane having an aromatic ring concentration of 0 mmol / g (hereinafter referred to as "polyurethane BU1") contained in the obtained polyurethane solution B1 was 14000, and the acid value of polyurethane BU1 was 40.0 mg-KOH / g. In addition, the solid content concentration in the polyurethane solution B1 was 45.0% by mass.

[0320] (Comparative Synthesis Example 2)

[0321] In a 1-liter three-necked flask equipped with a distillation apparatus, 611.0 g of bis[4-(2-hydroxyethoxy)phenyl]methane, 297.3 g of dimethyl isophthalate, and 0.5 g of dioctyltin oxide were added, and the methanol generated by heating at 180°C was distilled off under a nitrogen stream. After about 50 g of methanol was distilled off, the pressure in the reaction system was reduced to 1.3 kPa to accelerate the distillation rate of methanol. After the theoretical amount of methanol was distilled off, it was further heated for 1 hour, and after being maintained at 185°C-0.13 kPa for 1 hour, the reactor was cooled to obtain 810 g of polyester polyol (hereinafter referred to as polyester diol (β)). The hydroxyl value of the obtained polyester diol (β) was measured, and the hydroxyl value was 55.4 mg-KOH / g.

[0322] In a reaction container equipped with a stirring device, a thermometer and a condenser, 11.0 g of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (manufactured by Osaka Gas Chemical Co., Ltd., trade name: BPEF), 61.52 g of polyester diol (β), 6.32 g of 2,2-dihydroxymethylpropionic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a carboxyl group-containing diol, and 135.6 g of γ-butyrolactone as a solvent were added, and the mixture was heated to 100° C. to dissolve all the raw materials.

[0323] The temperature of the reaction solution was lowered to 90°C, and 27.00 g of diphenylmethane-4,4'-diisocyanate (manufactured by SUMIKA BAYER URETHANE Co., Ltd., trade name: MDI) as a polyisocyanate compound was added several times over 30 minutes using a dropping funnel. The reaction was carried out at 145°C to 150°C for 15 hours, and after confirming by IR that the absorption of C=O stretching vibration derived from the isocyanate group was almost not observed, 1.5 g of ethanol (manufactured by Wako Pure Chemical Industries, Ltd.) and 23.9 g of diethylene glycol diethyl ether (manufactured by Nippon Emulsifier Co., Ltd.) were added dropwise, and then the reaction was carried out at 80°C for 3 hours to obtain a solution containing a polyurethane having a carboxyl group and an aromatic ring concentration of 6.9 mmol / g (hereinafter referred to as "polyurethane solution B2").

[0324] The viscosity of the obtained polyurethane solution B2 was 125000 mPa·s. The number average molecular weight of the polyurethane having carboxyl groups and an aromatic ring concentration of 6.9 mmol / g (hereinafter referred to as "polyurethane BU2") contained in the polyurethane solution B2 was 20000, and the acid value of polyurethane BU2 was 25.0 mg-KOH / g.

[0325] The solid content concentration in the polyurethane solution B2 was 40.0% by mass.

[0326] Table 1 also shows the properties of polyurethanes AU1 to AU3 and polyurethanes BU1 to BU2.

[0327] [Table 1]

[0328] Polyurethane AU1 AU2 AU3 BU1 BU2 Number average molecular weight 20000 20000 20000 14000 20000 Acid value mg-KOH / g 25.0 10.6 25.0 40.0 25.0 Aromatic ring concentration m-mol / g 3.1 5.6 0.4 0 6.9

[0329] <Manufacturing of main agent compound>

[0330] (Implementation Example 1)

[0331] 160.0 parts by mass of polyurethane solution A1, 6.3 parts by mass of silica powder (manufactured by AEROSIL Japan, trade name: AEROSIL R-974), 0.72 parts by mass of melamine (manufactured by Nissan Chemical Industries, Ltd.) as a curing accelerator, and 8.4 parts by mass of diethylene glycol diethyl ether were mixed, and the silica powder and the curing accelerator were mixed into the polyurethane solution A1 using a three-roll mill (manufactured by Inoue Seisakusho, Ltd., model: S-43 / 4×11). Then, 2.0 parts by mass of a defoamer (olefin defoamer containing polyolefin, manufactured by BYK-CHEMIE JAPAN, trade name: BYK-1791) was added and mixed using a spatula. This mixture was used as the main agent mixture C1.

[0332] (Implementation Example 2)

[0333] 160.0 parts by mass of polyurethane solution A1, 6.3 parts by mass of silica powder (manufactured by AEROSIL Co., Ltd., trade name: AEROSIL R-974), 1.0 parts by mass of hydrotalcite (manufactured by Kyowa Chemical Industry Co., Ltd., trade name: DHT-4A), 0.72 parts by mass of melamine (manufactured by Nissan Chemical Industry Co., Ltd.) as a curing accelerator, and 8.4 parts by mass of diethylene glycol diethyl ether were mixed, and the silica powder and the curing accelerator were mixed into the polyurethane solution A1 using a three-roll mill (manufactured by Inoue Seisakusho Co., Ltd., model: S-4 3 / 4×11). Then, 2.0 parts by mass of a defoamer (olefin defoamer containing polyolefin, manufactured by BYK-CHEMIE JAPAN Co., Ltd., trade name: BYK-1791) was added and mixed using a spatula. This mixture was used as the main compound C2.

[0334] (Implementation Examples 3 to 7)

[0335] The same method as in Example 1 was used to prepare the mixture according to the composition shown in Table 2. The mixtures prepared in Examples 3 to 7 were respectively used as main mixtures C3 to C7. It should be noted that the numerical values ​​in the table represent "parts by mass." In addition, "DISPARLON 230HF" is an acrylic defoamer containing an acrylic resin, and "TSA750S" is a polysiloxane defoamer containing a polysiloxane resin.

[0336] (Comparative Matching Example 1)

[0337] 140.0 parts by mass of polyurethane solution B1, 5.5 parts by mass of silica powder (manufactured by AEROSIL Japan, trade name: AEROSIL R-974), 0.72 parts by mass of melamine (manufactured by Nissan Chemical Industries, Ltd.) as a curing accelerator, and 8.4 parts by mass of diethylene glycol diethyl ether were mixed, and the silica powder and the curing accelerator were mixed into the polyurethane solution B1 using a three-roll mill (manufactured by Inoue Seisakusho, Ltd., model: S-4 3 / 4×11). Then, 2.0 parts by mass of a defoamer (olefin defoamer containing polyolefin, manufactured by BYK-CHEMIE JAPAN, trade name: BYK-1791) was added and mixed using a spatula. This mixture was used as the main agent mixture D1.

[0338] (Comparative Matching Example 2)

[0339] The same method as in Example 1 was used to prepare the mixture according to the composition shown in Table 2. The mixture prepared in Comparative Example 2 was used as the main ingredient mixture D2. In addition, the numerical values ​​in the table represent "parts by mass."

[0340] (Comparative Matching Example 3)

[0341] The same method as in Example 1 was used to prepare the mixture according to the composition shown in Table 2. The mixture prepared in Comparative Example 3 was used as the main ingredient mixture D3. It should be noted that the values ​​in the table represent "parts by mass." [Table 2]

[0342]

[0343] <Manufacturing of Curing Agent Solution>

[0344] (Compounding Example 1 of Curing Agent Solution)

[0345] 16.85 parts by mass of an epoxy resin having a structure of the following formula (6) (manufactured by Mitsubishi Chemical Corporation, grade name: jER (registered trademark) 604, epoxy equivalent 120 g / eq v) and 18.25 parts by mass of diethylene glycol diethyl ether were added to a container equipped with a stirrer, a thermometer and a condenser, and stirring was started.

[0346] While continuing to stir, the temperature in the container was raised to 40°C using an oil bath. After the internal temperature was raised to 40°C, stirring was continued for 30 minutes. Then, it was confirmed that jER (registered trademark) 604 was completely dissolved, and the mixture was cooled to room temperature to obtain a solution containing jER (registered trademark) 604 with a concentration of 48% by mass. This solution was referred to as curing agent solution E1.

[0347] [Chemical formula 26]

[0348]

[0349] (Compounding Example 2 of Curing Agent Solution)

[0350] 16.85 parts by mass of an epoxy resin containing N,N-diglycidyl-4-(glycidyloxy)aniline as a main component (manufactured by Mitsubishi Chemical Corporation, grade name: jER (registered trademark) 630, epoxy equivalent 98 g / eqv) and 18.25 parts by mass of diethylene glycol diethyl ether were added to a container equipped with a stirrer, a thermometer, and a condenser, and stirring was started.

[0351] While continuing to stir, the temperature in the container was raised to 40°C using an oil bath. After the internal temperature was raised to 40°C, stirring was continued for 30 minutes. Then, it was confirmed that jER (registered trademark) 630 was completely dissolved, and the mixture was cooled to room temperature to obtain a solution containing jER (registered trademark) 630 with a concentration of 48% by mass. This solution was used as curing agent solution E2.

[0352] <Mixing of the main agent compound and the solution containing the curing agent>

[0353] (Compounding Example 1 of Curable Composition)

[0354] 88.7 parts by mass of the main agent compound C1 and 3.5 parts by mass of the curing agent solution E1 were placed in a plastic container. In addition, in order to make the viscosity consistent with the curable composition of other matching examples and comparative matching examples described later, 3.0 parts by mass of diethylene glycol diethyl ether and 1.5 parts by mass of diethylene glycol monoethyl ether acetate were added as solvents. The curable composition (hereinafter referred to as "curable composition F1") was obtained by stirring at room temperature for 5 minutes using a spatula.

[0355] (Compounding Examples 2 to 8 of Curable Compositions)

[0356] The curable composition was formulated in the same manner as in Formulating Example 1 to obtain the formulations shown in Table 3. The formulations prepared in Formulating Examples 2 to 8 of the curable composition were designated as curable compositions F2 to F8, respectively.

[0357] (Comparative formulation example 1 of curable composition)

[0358] 78.6 parts by mass of the main agent compound D1 and 5.6 parts by mass of the curing agent solution E1 were placed in a plastic container. In addition, in order to make the viscosity consistent with the curable composition of other formulation examples and comparative formulation examples, 4.8 parts by mass of diethylene glycol diethyl ether and 1.3 parts by mass of diethylene glycol monoethyl ether acetate were added as solvents. The mixing was carried out by stirring at room temperature for 5 minutes using a spatula to obtain a curable composition (hereinafter referred to as "curable composition G1").

[0359] (Comparative formulation example 2 of curable composition)

[0360] A curable composition (hereinafter referred to as “curable composition G2”) was prepared according to the formulation shown in Table 3 in the same manner as in the “Comparative formulation example 1 of curable composition”.

[0361] (Comparative formulation example 3 of curable composition)

[0362] A curable composition (hereinafter referred to as “curable composition G3”) was prepared according to the formulation shown in Table 3 in the same manner as in the “Comparative formulation example 1 of curable composition”.

[0363] The composition of each main component compound of curable compositions F1 to F8 and curable compositions G1 to G3 with the polyurethane solution is described in Table 3. In addition, the composition of each component of curable compositions F1 to F8 and curable compositions G1 to G3 is summarized in Table 4.

[0364] "a / (a+c)" in Table 4 represents the content (mass %) of component a relative to the total amount of component a and component c.

[0365] "b / (a+b+c)" in Table 4 represents the content (mass %) of component b relative to the total amount of component a, component b, and component c.

[0366] "(d+e)" in Table 4 represents the total amount (mass %) of component d and component e in the curable composition.

[0367] "(d+e) / (total amount of composition-b)" in Table 4 represents the total amount of component d and component e when the total amount of the components excluding the content of component b from the total amount of the curable composition is taken as 100 parts by mass.

[0368] "e / d" in Table 4 represents the content ratio (mass %) of component e relative to component d.

[0369] [Table 3]

[0370]

[0371] [Table 4]

[0372]

[0373] (Examples 1 to 8, Comparative Examples 1 to 3)

[0374] Using curable compositions F1 to F8 and curable compositions G1 to G3, disconnection inhibition, warpage, flexibility, and defoaming time were evaluated by the methods described below.

[0375] <Evaluation of Disconnection Suppression of Wiring of Wiring Board (MIT Test)>

[0376] A flexible wiring board having a fine comb-shaped pattern substrate (copper wiring width / copper wiring interval = 15 μm / 15 μm) described in JPCA-ET01 and tinned by etching a flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: SPERFLEX US, copper thickness: 8 μm, polyimide thickness: 38 μm) was coated with a tinning treatment, and the curable composition F1 was applied by screen printing so that the thickness of the printed film from the wiring surface was 5 μm (after drying). The printed film-formed wiring board was placed in a hot air circulation dryer at 80°C for 30 minutes, and then placed in a hot air circulation dryer at 120°C for 120 minutes, thereby curing the printed film.

[0377] Using this test piece, the test was carried out according to the method described in JIS C-5016 under the following test conditions.

[0378] (Test conditions)

[0379] Testing machine: MIT TESTER BE202 manufactured by TESTER Industry Co., Ltd.

[0380] Bending speed: 10 times / minute

[0381] Load: 200g

[0382] Bending angle: ±90°

[0383] Radius of the front end of the fixture: 0.5mm

[0384] The number of bendings was increased by 10 times under the test conditions, and the wiring was visually observed for cracks, and the number of bendings when cracks occurred was recorded. The results are recorded in Table 5.

[0385] In addition, the same evaluation was performed using curable compositions F2 to F8 and curable compositions G1 to G3. These results are also shown in Table 5.

[0386] <Evaluation of Warpage>

[0387] The curable composition F1 was applied to the substrate by screen printing using a #180 mesh polyester plate, and the substrate was placed in a hot air circulation dryer at 80°C for 30 minutes. Then, the substrate was placed in a hot air circulation dryer at 120°C for 60 minutes to cure the applied curable composition F1. As the substrate, a 25 μm thick polyimide film [Kapton (registered trademark) 100EN, manufactured by DuPont Toray Co., Ltd.] was used.

[0388] Apply the curable composition, use a hot air circulation dryer to cut the cured film into The shape cut into a circle presents a deformation of a convex or concave shape warped near the center. The sample formed with a cured film on the substrate obtained by cutting with a circular knife is left to stand in a downward convex state, that is, in contact with a horizontal plane near the center of the sample formed with a cured film on the substrate after 1 hour, and the maximum and minimum values ​​of the height of the warping from the horizontal plane are measured to obtain the average value. The symbol represents the direction of the warping. When left to stand in a downward convex state, the situation where the cured film becomes the upper side relative to the copper substrate or the polyimide film is set to "+", and the situation where the cured film becomes the lower side is set to "-." Then, if the warping is less than +3.0mm, it is qualified. The results are recorded in Table 5.

[0389] In addition, the same evaluation was performed using curable compositions F2 to F8 and curable compositions G1 to G3. These results are also shown in Table 5.

[0390] <Evaluation of Flexibility>

[0391] On the copper of the flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: SPERFLEX, copper thickness: 8μm, polyimide thickness: 38μm), the curable composition F1 was applied by screen printing to a size of 75mm in width, 110mm in length, and a film thickness of 15μm after curing, kept at room temperature for 10 minutes, and placed in a hot air circulation dryer at 120°C for 60 minutes to cure it. The PET film of the lining of the prepared test piece was peeled off, cut into a strip with a width of 10mm with a cutter, bent about 180 degrees in a way that the cured film surface became the outside, and compressed for 3 seconds at 0.5±0.2MPa using a compressor. Observe with a 30x microscope in a bent state to confirm whether cracks are generated.

[0392] The flexibility of curable compositions F1 to F8 was evaluated, and the results were all "no cracking." On the other hand, the flexibility of curable compositions G1 to G3 was evaluated, and the results were "no cracking" for G1 and G3, but "cracking" for G2.

[0393] <Defoaming time>

[0394] On the copper of a flexible copper-clad laminate (manufactured by Sumitomo Metal Mining Co., Ltd., grade name: SPERFLEX, copper thickness: 8 μm, polyimide thickness: 38 μm), the curable composition F1 was applied by screen printing to a size of 75 mm in width and 110 mm in length, and a film thickness of 15 μm after curing. At this time, the bubbles on the surface of the coating film were visually observed, and the time after the completion of screen printing was taken as 0 seconds, and the time until the bubbles disappeared was measured as the defoaming time.

[0395] In addition, the same evaluation was performed using curable compositions F2 to F8 and curable compositions G1 to G3. These results are also shown in Table 5.

[0396] [Table 5]

[0397]

[0398] From the above results, it was confirmed that the curable composition of the present example was excellent in at least disconnection suppression, low warpage, flexibility and defoaming property, and the cured product was useful as an insulating protective film for a flexible wiring board or the like.

Claims

1. A curable composition containing no fluorine atoms, comprising: (Component a) a polyurethane having a carboxyl group and an aromatic ring concentration of 0.1 to 6.5 mmol / g, and containing an organic residue derived from a polyisocyanate; (component b) a solvent; (Component c) a compound having two or more epoxy groups in one molecule; and (Component d) A first defoaming agent comprising an olefin.

2. The curable composition according to claim 1, wherein Component a is a polyurethane having a structural unit represented by formula (1), [Chemical formula 1] 3. The curable composition according to claim 1 or 2, wherein Component a is a polyurethane having a structural unit represented by formula (2), [Chemical formula 2] In the formula, R 1 Each independently represents a phenylene group or a phenylene group having a substituent.

4. The curable composition according to claim 1 or 2, wherein Component a is a polyurethane having a structural unit represented by formula (3), [Chemical formula 3] In the formula, n R 1 Each independently represents a phenylene group or a phenylene group having a substituent, and (n+1) R 2 Each independently represents an alkylene group having 3 to 9 carbon atoms, and n is a natural number of 50 or less.

5. The curable composition according to claim 1 or 2, wherein In component a, the organic residue derived from the cyclic aliphatic polyisocyanate accounts for 70 mol% or more of the total amount of the organic residue derived from the polyisocyanate.

6. The curable composition according to claim 1 or 2, wherein The content of component a is 60 to 99.9% by mass based on the total amount of component a and component c.

7. The curable composition according to claim 1 or 2, wherein The content of component b is 25 to 75% by mass based on the total amount of component a, component b and component c.

8. The curable composition according to claim 1 or 2, wherein The number average molecular weight of component a is 3,000 to 50,000, and the acid value of component a is 10 to 70 mgKO H / g.

9. The curable composition according to claim 1 or 2, further comprising: (Component e) A second defoaming agent comprising an acrylic resin and / or a methacrylic resin.

10. The curable composition according to claim 9, wherein The total amount of component d and component e is 0.01 to 3% by mass.

11. The curable composition according to claim 9, wherein When the total amount of the components excluding the content of the component b from the total amount of the curable composition is taken as 100% by mass, the total amount of the components d and e is 0.01 to 5% by mass.

12. The curable composition according to claim 9, wherein The content of component e is 1 to 150% by mass based on component d.

13. The curable composition according to claim 1 or 2, further comprising: (Component f) At least one type of fine particles selected from inorganic fine particles and organic fine particles.

14. The curable composition according to claim 13, wherein Component f includes silicon dioxide fine particles.

15. The curable composition according to claim 13, wherein Component f comprises hydrotalcite particles.

16. A cured product, which is a cured product of the curable composition according to claim 1 or 2.

17. An outer coating film for a flexible wiring board, comprising the cured product according to claim 16. 18 . A flexible wiring board obtained by forming wiring on a flexible substrate, wherein a part or the whole of a surface of the flexible wiring board on which wiring is formed is covered with the overcoat film for a flexible wiring board according to claim 17 .

19. A method for manufacturing a flexible wiring board covered with an outer coating film, comprising: (Step A) a step of forming a printed film on a flexible wiring board having wiring formed on a flexible substrate by printing the curable composition according to claim 1 or 2 on a part or the whole of a surface on which wiring is formed; (Step B) a step of evaporating part or all of the solvent in the printed film by placing the printed film obtained in step A in an atmosphere of 40° C. to 100° C.; and (Step C) A step of curing the printed film obtained in the step A or the printed film obtained in the step B by heating at 100° C. to 170° C. to form an overcoat film.

Citation Information

Patent Citations

  • Curable polyurethane composition

    JP1993247161A

  • Curable composition, cured object, overcoat film, coated flexible wiring board, and process for producing same

    CN108368336A

  • Production method of thermosetting resin composition and use of the same

    JP2017206591A

  • Defoaming agent

    JP2018118207A

  • Curable composition, cured object, overcoat film, coated flexible wiring board, and process for producing same

    WO2017110326A1